Order-disorder transitions in the Fe2VAl Heusler alloy. (December 2016) - Maier, S.; Denis, S.; Adam, S.; Crivello, J.-C.; Joubert, J.-M.; Alleno, E.
Abstract: A Rietveld analysis of neutron powder diffraction patterns obtained in situ during temperature scans shows that Fe2 VAl crystallizes at room temperature in the fully ordered L 21 structure and transforms at 1080 °C and at 1190 °C into partially disordered B 2 and fully disordered A 2 variants respectively. The low temperature stability of the L 21 structure as well as the two high temperature L 21 → B 2 → A 2 transitions are theoretically predicted by a combination of ab-initio (electronic structure and phonons) and thermodynamic calculations performed on special quasi-random structures. Pronounced cold work effects and the pre-transitional antisite defects which are observed respectively at 25 °C under mechanical stress and at high temperature (above 800 °C), appear to be generic effects in the family of Heusler alloys. Graphical abstract: